2018
DOI: 10.1093/cercor/bhy285
|View full text |Cite
|
Sign up to set email alerts
|

Direct Electrophysiological Correlates of Body Ownership in Human Cerebral Cortex

Abstract: Over the past decade, numerous neuroimaging studies based on hemodynamic markers of brain activity have examined the feeling of body ownership using perceptual body-illusions in humans. However, the direct electrophysiological correlates of body ownership at the cortical level remain unexplored. To address this, we studied the rubber hand illusion in 5 patients (3 males and 2 females) implanted with intracranial electrodes measuring cortical surface potentials. Increased high-γ (70–200 Hz) activity, an index o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
54
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 63 publications
9
54
1
Order By: Relevance
“…It should also be noted that the present behavioral results are consistent with neuroimaging studies that have demonstrated activity in frontal and parietal areas related to the integration of visual, tactile, and proprioceptive signals (Gentile, Guterstam, Brozzoli, & Ehrsson, 2013;Limanowski & Blankenburg, 2016) during the RHI (Ehrsson et al, 2004;Guterstam et al, 2019) and that the strength of this activation correlates with the strength of hand ownership as rated in questionnaires (Ehrsson et al, 2004;Gentile et al, 2013;Guterstam et al, 2013). Future fMRI studies could use the current psychophysical approach to examine whether the activity in these areas follows the same psychometric curves as the behavioral discriminations, and future transcranial magnetic stimulation studies could use the current approach as a sensitive method to test whether transient perturbation of the neural processing in these areas affects the perceptual ownership discriminations.…”
Section: Refining Knowledge Of the Spatial And Temporal Constraints Osupporting
confidence: 92%
“…It should also be noted that the present behavioral results are consistent with neuroimaging studies that have demonstrated activity in frontal and parietal areas related to the integration of visual, tactile, and proprioceptive signals (Gentile, Guterstam, Brozzoli, & Ehrsson, 2013;Limanowski & Blankenburg, 2016) during the RHI (Ehrsson et al, 2004;Guterstam et al, 2019) and that the strength of this activation correlates with the strength of hand ownership as rated in questionnaires (Ehrsson et al, 2004;Gentile et al, 2013;Guterstam et al, 2013). Future fMRI studies could use the current psychophysical approach to examine whether the activity in these areas follows the same psychometric curves as the behavioral discriminations, and future transcranial magnetic stimulation studies could use the current approach as a sensitive method to test whether transient perturbation of the neural processing in these areas affects the perceptual ownership discriminations.…”
Section: Refining Knowledge Of the Spatial And Temporal Constraints Osupporting
confidence: 92%
“…Our results are also consistent with a human electrocorticogram study, that showed sustained high-γ activity in the premotor cortex reflected the feeling of ownership during the rubber-hand illusion. Instead, high-γ activity locked to the tactile stimulus (but not to the illusion itself) was more closely localized to the posterior cortex (31).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the upper limit of the gamma band frequency was decided based on the finding that the high frequency band (> 60 Hz) activity was functionally differentiated from the low (30–60 Hz) gamma 38 . Although higher gamma power has been observed in intracranial EEG recordings during the RHI 39 , we focused on the lower gamma band because the scalp EEGs with HMD are susceptible to noise. For each target component, we averaged all values across time and frequency points and obtained one value for each condition and participant.…”
Section: Methodsmentioning
confidence: 99%